Implementasi SAK ETAP Pada Sistem Pencatatan Pengelolaan Air Bersih Di Desa Dawung Kelurahan Kedungpane Kecamatan Mijen Kota Semarang - Ratih Diyah Ramadani; Faris Shalahuddin Zakiy (Jurnal Akuntansi dan Audit Syariah (JAAiS), 2022)
Dawung Village, the underestimated district is one of the villages in Mijen, Semarang City is one of the villages that manages clean water independently. Clean water is obtained from wells located near mosques and prayer rooms. Meanwhile, financial records are still done manually by writing each resident's monthly bill on a piece of paper. In this digitalization era, the use of physical data is more at risk of being damaged. So the need for renewal by replacing the data that was previously manual to automatic based on digital data and the application of SAK ETAP standards. This study aims to assist the Dawung Village community in recording clean water management. The method used is interviews with PAM administrators in Dawung Village. From the explanation, it was found that Dawung Village had to update the data by changing it from manual to automatic based on digital data. In addition, training is needed for administrators to be able to understand and implement SAK ETAP in the financial management of PAM in Dawung Village. Empowerment of village youth can also be carried out to support the improvement of financial management at PAM Dawung Village